The Impact Of Revolution 5.0 on Digital Government and Public Service Efficiency - Isra Muksin; Mansyur Djamal; Jacky Chin; Yunus Arifien (Nomico, 2024)
This study explores the impact of Revolution 5.0 on public service efficiency in the context of digital governance. The primary aim of the research is to assess how advanced technologies such as Artificial Intelligence (AI), Big Data, and the Internet of Things (IoT) are influencing the performance and efficiency of government services. This study uses a quantitative research approach, employing a descriptive and explanatory design to describe the phenomenon and analyze the relationship between Revolution 5.0 technologies (independent variable) and public service efficiency (dependent variable). Data were collected through a survey administered to 250 respondents, including government employees, State Civil Apparatus (ASN), and the public, using a structured questionnaire with Likert scale items. The findings indicate that the integration of digital technologies significantly enhances administrative efficiency, reduces processing time, and improves public satisfaction with government services. The study contributes valuable insights into the ongoing digital transformation in public administration and provides recommendations for improving digital literacy among civil servants to further optimize service delivery.